cm biểu thức A=(x^n+1).((x^n-2)-x^n-3( x^n-3-x^3)+2007 k phụ thuộc vào x

Question

cm biểu thức
A=(x^n+1).((x^n-2)-x^n-3( x^n-3-x^3)+2007
k phụ thuộc vào x

in progress 0
Quinn 1 năm 2021-08-07T18:03:23+00:00 1 Answers 6 views 0

Answers ( )

    0
    2021-08-07T18:05:11+00:00

    Đáp án:

     

    Giải thích các bước giải:

     A=($x^{n}$ +1).($x^{n}$ -2) -$x^{n}$ -3.($x^{n-3}$  -x³ )+2007

       =$x^{2n}$ -2$x^{n}$ +$x^{n}$ -2 -$x^{n}$ -3.$x^{n-3}$ -3x³ +2007

      =$x^{2n}$ – 2$x^{n}$  -3$x^{n-3}$ +3x³ +2007

    bạn xem lại đề.

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )